(untitled) (Al-Academy, 2025)
Artistic trends, from their first beginnings up to post-modernism, are considered a turning point towards change, diversity and innovation in the field of artistic production. This is what helped the artist to create different works of art, depending on the different mechanisms and new techniques of display that are different from what was previously seen and outside the norm and the approved values. In the past, they were adopted as expressive and aesthetic values that formed and diversified until they became contemporary styles and trends later, especially those arts that witnessed the post-modern period. These arts are considered an important and advanced step that worked to transform the artistic achievement in its general composition, into a stylistic structure based on synthesis. An aesthetic technique for a collection of objects taken from nature and manufactured by humans, who worked to transfer them into the artistic experience. Therefore, the researcher decided to delve into the content of the current study and answer the following question: (Was this radical transformation reflected in the performance of technical diversity in the students’ productions)? The current research consisted of four chapters. The first chapter included presenting the research problem, which centered on answering the following question. (Was this radical transformation reflected in the performance of technical diversity in students’ productions?) As the current research aims to (identify technical diversity in Abstract Expressionism and the extent of its uses in students’ productions). The second chapter, which includes the theoretical framework and consists of two sections, the first section: the concept of technology, and the second section: technical diversity in Abstract Expressionism, and the second chapter ended with indicators of the theoretical framework, while the third chapter includes the research methodology and procedures, as the current research aims to identify the diversity Technical approach to Abstract Expressionism. The researcher adopted the descriptive analytical approach as a methodological framework for building his research procedures, as it is the most appropriate scientific method to achieve the goal of the research, as the current research community consists of several artistic paintings, numbering (10) artistic paintings, where the sample of the current research was chosen, numbering in number. (3) Artistic paintings, which were chosen intentionally. The research produced a set of results, including: 1- Through the analysis of the samples of the current research, it became clear that all samples relied on technical diversity in forming the structure of the artwork, such as knives, trowels, and types of brushes, Blades, perforated cans for spraying colors, and pieces of sponge were used for wiping and creating a kind of color fusion as a new technique within the artwork. 2- All artists have used unfamiliar or accustomed materials in their artistic works, to create technical diversity in the space of the artistic work, such as wood, shattered glass, metals, heavy paint, distilled paint, sand, and other materials. The fourth chapter includes conclusions, including . 1-The use of technical diversity contributed significantly to addressing the artistic painting space, which led to innovation and distinction. 2- Abstract Expressionism was able to activate marginalized materials and benefit from technical developments in achieving artistic production.